Te Kāuru Hou—A New Leaf: Processing Harakeke (Phormium tenax) for WholeGarment® Knitting Technology – Shima Seiki - Alexander-Maaka, Kimberley (Auckland University of Technology, 2021)
There is demand for high-quality natural fabrics, which are cultivated and transformed by processes that are environmentally and culturally sustainable. In response to this demand, and underpinned by Te Ao Māori worldviews and environmental values, this research meticulously questions how can harakeke advance technology while maintaining her integrity? The development of new techniques and innovations are explored to transcend harakeke (phormium tenax) from harvest to a digitally knitted structure - something that has not been achieved before. The research specifically explores analogue (hand) and digital processes (WholeGarment® digital knitting technologies), the relationship of European sciences and Māori harakeke knowledges, and the interconnections between Raranga (weaving) and the textile design. The bridging of these areas give rise to opportunities for experimentation, creativity and innovation. This includes the development of new techniques for the successful processing and spinning of muka fibre using innovative binding solutions, combing and wave-set processes, and the knotting of fibre ends to create a fine yarn for further processing using digital knitting, as well as simple processes to soften the fibre after knitting. The findings demonstrate how techniques from the past and present can be synthesized to create new and unconventional textiles. They also show how Te Ao Māori worldviews can augment and extend scientific knowledge, and when integrated with design, can transform natural plant resources into innovative, sustainable materials and products.
Keywords: Harakeke; NZ Flax; Phormium Tenax; Shima Seiki; WholeGarment; Māori; Innovative Technology; Plant to Fibre; Te Ao Maori/European; Environment; Sustainable; Productivity; Textile/Fibre Technology; Identity